PENGARUH HASIL BELAJAR PEMBELAJARAN MIKRO TERHADAP KESIAPAN MENGAJAR MAHASISWA PLP FKIP UNIVERSITAS PANCASAKTI TEGAL - Marlinda, Widya Antika; Apriani, Dewi; Habibi, Beni; Nafiati, Dewi Amaliah (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Teacher education has a strategic role in producing professional educators who are ready to face the challenges of the world of education. One of the practice-based courses that aims to improve students' teaching competence is Micro Teaching. However, the effectiveness of micro learning learning outcomes in shaping students' teaching readiness has not been fully measured empirically. This study aims to determine the effect of micro teaching outcomes on the teaching readiness of PLP FKIP Universitas Pancasakti Tegal students, class of 2021. The study used a quantitative approach with a correlational design. The subjects of the study were 66 students selected through purposive sampling techniques from a total population of 195 students. Data were collected through observation, Likert-scale questionnaires, and documentation, then analyzed using descriptive statistical tests and partial t-tests with the help of SPSS version 27. The results showed that micro learning learning outcomes did not have a significant effect on teaching readiness, as indicated by a significance value of 0.985 and a calculated t of 0.019